SIKAP PNS TERHADAP NIAT MENGGUNAKAN SIMDA KEUANGAN DALAM PROSES PENGELOLAAN KEUANGAN DAERAH DI LINGKUNGAN PEMERINTAH BENGKULU TENGAH - Susanti, May; Fadli, Fadli; Coryanata, Isma (JURNAL FAIRNESS, 2013)
Information technology systems in establishing effective financial management includes budgeting, implementation / Business Management, and reporting and accountability are fast, accurate, and appropriate and in accordance with the regulations, it is necessary efforts to carry out financial management as expected above. Attempts to run the financial management to be effective so as to achieve results quickly, accurately, and proper and in accordance with the regulations can be achieved by the issuance of Regional Management Information System (SIMDA) made by the Financial Supervisory Agency of Finance and Development. This study aims to demonstrate empirically the effect of perceived usefulness on intention to use SIMDA Treasury civil servant in the Government Bengkulu Tengah and to demonstrate empirically the effect of perceived ease of use on intention PNS SIMDA Finance in the Government of Bengkulu Tengah. The research uses primary with in the form of questionnaires. Analyzed using multiple linear regression analysis.From the results of multiple linear regression testing can be concluded that the influence of perception Usefulness (H1) is positive and significant impact on intention to use SIMDA Finance so that the first hypothesis (H1) is accepted and the perceived ease result (H2) significant positive effect on intention to use SIMDA Finance, so The second hypothesis (H2)is accepted.